ANALYSIS OF EFFECTIVE THE MASTERY OF BUSINESS JAPANESE COMMUNICATION ON STUDENTS KNOWLEDGE AND INTERESTS - Miftachul Amri (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
It is necessary to develop an interest in learning good Japanese business communication in students. Considering the importance of learning interest in the learning process, teachers must pay attention to and develop this learning interest. The communication culture of Japanese society in general characterizes Japanese business communication in particular. Even though Japanese business communication is actually considered more complex, this is a derivative of the character of Japanese society itself. In learning Japanese, apart from being introduced to the communication culture, other cultures related to the Japanese business world should also be introduced. Some values in the Japanese business world are still closely held, but there are also values that have begun to be abandoned, one of which is loyalty. Japanese business communication culture in the form of group orientation can be introduced through learning jikoshokai 'self introduction' and meishi kokan 'exchanging business cards'. Apart from that, the expressions osewa ni narimashita and juju hyogen 'the expression give and receive' can be taught to introduce hierarchical culture. Meanwhile, horenso culture can be introduced through learning the N gurai Vru monda sentence pattern.